Pack up the moon ebook - Higgins, Kristan (2021)
Funny, heartbreaking and uplifting, New York Times bestselling author Kristan Higgins delivers an unforgettable romance about how love can transcend even the greatest obstacles. They used to joke about her “honey do” lists. He just never realized how much he would need one when she was gone. Being a widower is not something Joshua Park ever expected. Given his solitary job as a scientist, his small circle of friends and family, and the social awkwardness he’s always suffered from, Josh has no idea how to negotiate this new, unwanted phase of life.  But his beloved wife Lauren had a plan to keep him moving forward, to lead him on a journey through grief, anger, and denial—twelve letters. Twelve letters to see him through the first year without her, and to lead him on a heartrending, beautiful, often humorous journey to find joy again. From his first outing as a widower to buy groceries to finding a new best friend while sobbing in a clothing store, Joshua’s grief makes room for him to learn Lauren’s most valuable lesson: The path to happiness doesn’t follow a straight line. Emotional, heartwarming, and perfect for book clubs, TikTok sensation Pack Up the Moon illuminates how love always finds a way to carry bring us joy, even when we least expect it.